The relationship between body composition and physical fitness with primary dysmenorrhea among adolescents in urban areas - Rizki Purwaningtyas Desiani; Fitriani Anna; Darmawansyah Alnur Rony (BIO Web of Conferences)
Background: The relationship between body composition and physical fitness parameters with primary dysmenorrhea hasn’t been confirmed robustly to the best of our knowledge. Objective: This study analysed the relationship between nutritional status, body composition, and physical fitness with primary dysmenorrhea. Methods: This cross-sectional study involved 80 adolescents from urban areas of Jakarta, Bogor, Depok, Tangerang, and Bekasi Indonesia. Body composition indicators measured by the OMRON HBF 375-Karada Scan body analyser. The fitness components observed were cardiorespiratory fitness as measured by the 3- minute YMCA step test, abdominal muscle strength by 1-minute sit-ups, abdominal muscle endurance by plank, and flexibility by sit and reach. Dysmenorrhea was measured using the WaLLLID score questionnaire. Bivariate analysis used the Pearson Correlation Test with a significance level of 0.05. Results: All respondents experienced dysmenorrhea with varying levels, intensity, locations, and duration of pain. Visceral fat percentage was significantly related to duration of pain (P=0.007) while total subcutaneous and trunk fat was significantly related to pain intensity (P=0.049). Cardiorespiratory fitness was significantly related to the location of pain (P=0.016). Conclusions: Maintaining visceral, total subcutaneous, and subcutaneous trunk fat within normal limits and good cardiorespiratory fitness control menstrual pain.